IMPROVING THE LOGICAL THINKING ABILITY OF EARLY CHILDREN IN GROUP A THROUGH CONCRETE GROUPING MEDIA IN TRISULA PERWARI KINDERGARTEN - Fadhillah, Nur; Yulianty S, Nadya (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to improve the logical thinking ability of group A children through the use of concrete media for classifying at TK Trisula Perwari. Logical thinking skills are important to help children think systematically, recognize differences, and make simple classifications. The research was conducted using Classroom Action Research (CAR) with a cyclical model, carried out in two cycles, each consisting of two meetings. The subjects of the study were 8 children aged 4–5 years. Data were collected through observation and analyzed using a descriptive quantitative approach. The results showed that children’s logical thinking abilities increased after applying concrete media for classifying. The indicator of naming groups based on criteria increased by 25% (2 children), distinguishing large and small sizes rose by 25% (2 children), classifying objects by category improved by 37.5% (3 children), arranging simple patterns increased by 37.5% (3 children), and identifying the function of objects by category rose by 25% (2 children). By the end of the second cycle, all indicators had exceeded the minimum success criteria of 75%. It can be concluded that the use of concrete media for classifying is effective in enhancing the logical thinking ability of group A children at TK Trisula Perwari.